Globalization and Modernization in Developed and Developing Countries: Typical Features and Main Strategies: Глобализация и модернизация в развитых и развивающихся странах характерные черты и основные стратегии - Avdeev, Evgenii; Vorobiev, Sergey (Przegląd Wschodnioeuropejski, 2019)
The paper reviews the interconnection of globalization and modernization processes in developing countries. The typical features of the new stage of globalization, such as changing the direction of globalization, regionalization, formation of new global development centers, as well as other problems and contradictions in the main trends of globalization and their impact on the modernization processes in developing countries are discussed. The article analyzes the main strategies of modernization developing countries such as modernization based on the coercive, political and economic pressure of the Western world, leading to copying of socio-economic and political development models and institutions and a modernization strategy based on the convergence of global development models and national socio-economic models. The authors consider the main features of the entry into the world development of the countries of Eastern Europe on the basis of preserving state and socio-cultural integrity and defining their own specificity of entering into a single European community already formed